ANALISIS KINERJA LAPORAN KEUANGAN PADA PT. ASURANSI JIWASRAYA (PERSERO) - Manurung B11108131, Ferry Christian (Jurnal Manajemen Update, 2014)
This study describes the results of an analysis of the company's financial statements. This research is a form of qualitative research. Description of which is done through two methods, namely analysis, ratio analysis and horizontal analysis. Companies that become the object of research is PT Jiwasraya Insurance. Techniques of data collection in this research through the study of the documentation is to collect documents relating to the company's corporate finance and literary study conducted by collecting literature relating to the research. The results of this research are expected to demonstrate sejauhmana in the financial performance of PT Asuransi Jiwasraya for the last 5 years. In addition, also to find out the factors that influenced the change of the financial ratios of PT Asuransi Jiwasraya. From the results of the calculations are done to see that the financial performance of PT Asuransi Jiwasraya experienced fluctuating fortunes over the past 5 years (2007-2011). Keywords: financial report, financial ratio, financial performance